Air-stable metal hydride-polymer composites of Mg(NH2)2–LiH and TPX™. (December 2018) - Cao, Hujun; Georgopanos, Prokopios; Capurso, Giovanni; Pistidda, Claudio; Weigelt, Fynn; Chaudhary, Anna-Lisa; Filiz, Volkan; Tseng, Jo-Chi; Wharmby, Michael T.; Dornheim, Martin; Abetz, Volker; Klassen, Thomas
Abstract: Light metal hydrides are prone to react with oxygen and/or water to produce oxides and/or hydroxides leading to reduction of hydrogen capacities, and deterioration of the hydrogen storage properties. It is therefore critical to address these issues when the materials are to be exposed to air or moisture. In this work, the combination of light metal hydrides, Mg(NH2 )2 –nLiH with polymethylpentene (TPX™), an air/moisture protective barrier is presented. It was found that the fabricated composites exhibit significant improvement of the metal hydrides stability in air. No oxidation reactions in air can be proven even after air exposure for 90 min. Extending the air-exposure time to 12 h, the reversible hydrogen capacities of these composites are much higher and more stable than they are in the case of the pure metal hydrides. In comparison to the pure metal hydrides, the composites retain the same hydrogen loading capacities and kinetic properties, with respect to the metal hydrides contents. Further, in situ synchrotron radiation powder X-ray radiation diffraction (SR-PXRD) experiments reveal that the thermal decomposition reaction pathways of the 90 min air-exposed composites are the same under air or H2 atmosphere. Moreover, morphology analysis confirms that the metal hydrides remain stable in the polymeric matrix and the three-dimensional integrity is retained, even after performing tens of de/re-hydrogenation cycles. The present study shows a promising way to fabricate air-stable metal hydride-polymer composite hydrogen storage materials that can be handled in ambient conditions. Graphical abstract: The amide-hydride systems remain stable in the polymeric matrix of polymethylpentene significantly improving the air stability of the metal hydrides. It shows a promising way to fabricate metal hydride-polymer composite energy storage materials that can be handled in ambient conditions. Highlights: Air-stable metal hydride-polymer composites have been prepared. Metal hydride-polymer composites retain the same hydrogen loading capacities and kinetic properties as the pure hydrides. Metal hydrides maintain three-dimensional structural integrity in the polymeric matrix. Reaction mechanisms of the metal hydride-polymer composites in air and H2 have been investigated.